First detection of Toxoplasma gondii Africa 4 lineage in a population of carnivores from South Africa - Račka, Karol; Bártová, Eva; Hamidović, Azra; Plault, Nicolas; Kočišová, Alica; Camacho, Gerrie; Mercier, Aurelién; Halajian, Ali (Frontiers in Cellular and Infection Microbiology, 2024)
There have only been a few molecular studies conducted on the detection of T. gondii in tissues of carnivores in South Africa, with no data on the genetic diversity of this parasite. That is why the aim of this study was to detect and genotype T. gondii DNA in tissues of selected wild and domestic carnivores in South Africa.: Samples were collected from 80 animals of 20 species (mainly road-killed) in the four provinces of Limpopo (n=57), Mpumalanga (n=21), Gauteng (n=1) and Free State (n=1) during the period 2014-2018. Samples of brain (n=31), heart (n=4), liver (n=40), spleen (n=2) and lung (n=3) were used to detect T. gondii by real-time PCR targeting a 529 bp repeating fragment of T. gondii DNA. Samples that were positive in real-time PCR were genotyped using 15 microsatellite markers.Results: T. gondii DNA was detected in 4 (5 %) samples: in the brain from a Black-backed Jackal (Canis mesomeles), in the liver from a African Wildcat (Felis silvestris lybica) and in the liver and heart of two Rusty-spotted Genets (Genetta maculata) respectively. The DNA sample from Black-backed Jackal was genotyped and characterized as belonging to the type Africa 4 lineage (equivalent to RFLP genotype ToxoDB#20).Discussion: This is the first genetic characterization of T. gondii isolated from a wild carnivore on the African continent and the first report of T. gondii in Black-backed Jackal. The Africa 4 lineage was also confirmed in the region of Southern Africa for the first time.